Educational Resources for Preservice Anesthesia Training Programs in Amhara Region, Ethiopia - Yetneberk, Tikuneh (Adv Med Educ Pract, 2021)
BACKGROUND: Across low and middle-income countries, shortages of essential equipment, supplies, and human resources in health training institutions pose a problem to educational program delivery. With the rapid expansion of anesthesia training programs to address the shortages in anesthesia workforce, the need for educational resources has also grown. This study sought to evaluate the availability of educational resources within anesthesia degree programs in Ethiopia. METHODS: Utilizing the Higher Education Relevance and Quality Agency of Ethiopia standards, a questionnaire survey was designed and distributed to schools of anesthesia in the Amhara region. A total of 96 standard indicators were used to assess the attainment of preservice educational resources for non-physician anesthesia degree programs, of which 71 (74%) were basic standards and 25 (26%) were standards for quality improvement. RESULTS: Two of the six institutions delivering anesthesia training in the Amhara region responded to the questionnaire. Neither the basic nor the quality improvement standard requirements for educational resources were completely achieved in any category of classrooms, offices, skills laboratory, clinical practice site, information technology facilities, library, student amenities, or financial resource. The target achievement rate was 50% or below in all but one category (clinical practice site). CONCLUSION: Educational resources for responding preservice anesthesia training programs in the Amhara region of Ethiopia are inadequate and below the required national standards. Expansion of anesthesia training programs should be accompanied by the necessary resources for high quality program delivery and to ensure quantity does not compromise on quality.